Microscopic analysis of plant‐mediated silver nanoparticle toxicity in rainbow trout fish (Oncorhynchus mykiss). Issue 10 (28th May 2021) - Ali, Ihsan; Khan, Shuaib; Shah, Khadim; Haroon; Kalimullah; Bian, Liujiao
Abstract: Over the years, nanoscience and the application of nanomaterials have gained the attention of researchers due to their enormous application history. Especially, the application of AgNPs providing innovative solutions to a wide range of environmental issues, for instance, wastewater treatment, bioremediations, and environmental sensing. Besides all these, the environmental application of silver nanomaterials causes severe problems in the terrestrial and aquatic ecosystems. For their concern, the present study was conducted to expose rainbow trout fish ( Oncorhynchus mykiss ) to different concentrations of silver nanoparticles for 25 days. In the current study, mortality (LC50 ), accumulation, and histopathological changes were analyzed. The results have revealed that the silver nanoparticles were mostly accumulated in the liver followed by the intestine, gill, and muscles. The microscopic analysis has shown that the accumulation of silver nanoparticles led to histological changes in gill and intestinal tissues. Necrosis, degeneration, mucus substance on the surface of gill lamella, cell lysis, and gill lamella atrophy were found at (0.04 mg/L) and (0.06 mg/L). The findings in the current study showed less toxicity in the sense of mortality and accumulation of AgNPs. Therefore, further systematic studies are needed to access the influence of silver nanoparticles on the aquatic ecosystem. Abstract : The AgNPs were significantly fabricated. The AgNPs cause toxicity in the environment. The AgNPs were mainly accumulated in the liver. The accumulation led to histopathological changes in tissue.